Language Comprehensibility Analysis of Digital Educational Content on Solar Power Generation for Non-Technical Communities - Ghina Syamilah; Mujibur Rohman; Siti Nuranisa Mulyadi; Teuku Fazrilah Arbaizan; Wiranadi Ramdhani; Mochamad Whilky Rizkyanfi (International journal of technology and education research, 2026)
The lack of energy literacy among the Indonesian public significantly hinders the adoption of Solar Power Plants, which has only reached 13.09% of the renewable energy mix target by the end of 2023. This study aims to analyze the level of language comprehensibility in digital educational content on PLTS intended for non-technical audiences, using a qualitative descriptive approach through a systematic literature study. Data analysis was conducted using content analysis techniques supported by readability formulas, namely Flesch Reading Ease, Gunning Fog Index, and SMOG. The findings indicate that content produced by official institutions generally falls into the